Structure Analysis and Morality in the Fables “The Wind and the Sun” by Aesop - I Gede Kana Wiranata; Ida Bagus Gde Nova Winarta (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This research aims to analyze one classic fables by Aesop, namely “The Wind and The Sun” The main focus of this study is to understand the narrative functions of these fables and to identify the characters within them. The approach used in this analysis is Vladimir Propp's (1928) structuralism theory, which has proven effective in analyzing the narrative structure of folktales and fables. Propp (1928) suggests that narratives can be broken down into several basic functions that help understand how stories are constructed. Data for this study is sourced from the English language textbook, The Roberts English Series: A Linguistics Program, book 3, which contains various fables used as teaching materials. The study delves deeply into these fables, meticulously following the theoretical framework mention while “The Wind and The Sun” illustrates the power of persuasion compared to force. This study provides profound insights into how fables are used as pedagogical tools to teach moral and ethical values to young readers.